A Systematic Literature Review on Performance Evaluation of Power System From the Perspective of Sustainability - Deng, Deqiang; Li, Chao; Zu, Yafei; Liu, Lana Yan Jun; Zhang, Jiayang; Wen, Subin (Frontiers in Environmental Science, 2022)
Sustainability is a comprehensive concept that integrates at least three dimensions of environment, economy and society. The power system is the primary source of greenhouse gas emissions, adversely impacting environmental sustainability. It also generates necessary energy supplies, which promote economic and social sustainable development. Based on the sustainability nature of power system, this study puts forward an improved methodology, namely ‘Planning-Searching-Screening-Reporting-Reflecting’ (PSSRR Cycle) to review the literature systematically on power system performance evaluation from a sustainability perspective over the past 20 years, with the aim of describing the current state of the whole performance evaluation system including the evaluation framework, evaluation indicators and evaluation methods, and providing research suggestions for future research. This study finds in the current literature that the Triple Bottom Line theory is the most commonly used theoretical evaluation framework; environmental and economic sustainability indicators are more emphasized; the DEA and MCDM methods are the more common evaluation methods. This study presents some future research notes, including improving the Sustainable Balanced Scorecard as a sustainable performance evaluation framework, emphasising more social sustainability indicators, and using a combination of existing evaluation methods to make performance evaluation more efficient and accurate.